Hybrid GLAss-Steel Stele (HYGLASS): Preliminary Mechanical Study on a Smart Tetrahelical Cantilevering Tall Structure - Maurizio Froli (Challenging Glass Conference, 2018)
Future smart cities are demanding for new infrastructures and networks. Novel multifunctional objects should be able to acquire, store and transmit information, generate their own energy need, light up the surroundings and more.  Thanks to their transparency, glass structures are ideal support for hi-tech components because of the inherent opportunity offered by laminated glass to embed PV cells, sensors, OLEDs and lighting devices. The project HYbrid GLAss-Steel Stele (HYGLASS) aims at the realization of a cantilevering hybrid vertical structure working as a stand-alone or a grid-connected smart tower. The facetted geometry of the construction originates from the tetrahelix solid, and its structural conception is based on segmentation and post-tensioning, which are the same basic principles of the Travi Vitree Tensegrity (TVT). The spatial complexity and the height of the tower (about 7.00 meters) requires a high ULS safety level that is obtained by designing the structure to withstand the worst-case scenario of all panels cracked. To this purpose and to facilitate the assembly operations, a filigree metal skeleton is placed at the edges of the base polyhedron. Equal triangular glass panels are corner clamped into special nodes at the vertices of the solid. Modularity and dry connections facilitate an easy replacement of the damaged components. FE nonlinear analyses highlight the safe design and efficiency of the system. Such structural concept is the key to extent the hybrid glass-steel construction to the domain of self-supporting high-rise and long-spanned structures or building skins.